Kajian Pengelolaan Instalasi Pengolahan Air Limbah di Rumah Sakit - Difana Meilani; Mohammad Hanif (Universitas Andalas, 2019)
Risk management is a process of knowing, analyzing, and controlling risks of every activity in product and, service sectors. The aims are the process runs effectively and efficiently. One of the ISO studies on risk management has been guided in ISO 31000. This ISO provides a standard framework with the title